Improving the System of Teaching Foreign Languages - Kambarova Dilnoza Musakulovna; Isamuxamedova Munisxon Najmitdinovna (Research Parks Publishing LLC, 2021)
In this article we can see that the main focus now is on the study and teaching of foreign languages, as well as its further development and comprehensive improvement. In addition, there are many decisions based on it in the study of foreign languages. At the same time, foreign languages are very important today.